Genetic Heterogeneity in Bartter Syndrome: Clinical and Practical Importance - Laura Florea; Lavinia Caba; Eusebiu Vlad Gorduza (Frontiers Media S.A., 2022)
Bartter syndrome (BS) is a rare tubulopathy that causes polyuria, hypokalemia, hypochloremic metabolic alkalosis, and normotensive hyperreninemic hyperaldosteronism. It is characterized by locus, clinical, and allelic heterogeneity. Types 1-4 of BS are inherited according to an autosomal recessive pattern, while type 5, which is transient, is X linked. There are specific correlations between the clinical expression and the molecular defect, but since it is a rare disease, such studies are rare. Therapeutic interventions are different, being correlated with types of BS.